Allopathic and traditional health practitioners' collaboration - Dalena van Rooyen; Blanche Pretorius; Nomazwi M. Tembani; Wilma ten Ham (AOSIS, 2015)
Background: Professional collaboration between traditional and allopathic health practitioners in South Africa is proposed in the Traditional Health Practitioners Act and could benefit and complement healthcare delivery. Objectives: To explore and describe the collaborative relationship between allopathic and traditional health practitioners regarding the legalisation of traditional healing, and these health practitioners' views of their collaborative and professional relationship, as role-players in the healthcare delivery landscape in South Africa. Methods: A qualitative design was followed. The research population comprised 28 participants representing three groups: allopathic health practitioners (n = 10), traditionalhealers (n = 14), and traditional healers who are also allopathic health practitioners (n = 4). Purposive and snowball sampling was used. Data collection involved unstructured interviews, a focus group interview and modified participant observation. Results: Results indicate both allopathic and traditional health practitioners experienced negative attitudes towards each other. Mutual understanding (in the form of changing attitudes and communication) was considered crucial to effective collaboration between these two health systems. Participants made suggestions regarding capacity building. Conclusions: Considering realities of staff shortages and the disease burden in South Africa, facilitating collaboration between allopathic and traditional health practitioners is recommended. Recommendations could be used to develop strategies for facilitating professional collaboration between traditional and allopathic health practitioners in order to complement healthcare delivery.